3D Nitrogen‐Doped Graphene Encapsulated Metallic Nickel–Iron Alloy Nanoparticles for Efficient Bifunctional Oxygen Electrocatalysis. Issue 18 (19th February 2020) - Wang, Zhaoyang; Liao, Xiaobin; Lin, Zifeng; Huang, Fuzhi; Jiang, Yalong; Owusu, Kwadwo Asare; Xu, Lin; Liu, Ziang; Li, Jiantao; Zhao, Yan; Cheng, Yi‐Bing; Mai, Liqiang
Abstract: It is extremely desirable to explore high‐efficient, affordable and robust oxygen electrocatalysts toward rechargeable Zn–air batteries (ZABs). A 3D porous nitrogen‐doped graphene encapsulated metallic Ni3 Fe alloy nanoparticles aerogel (Ni3 Fe‐GA1 ) was constructed through a facile hydrothermal assembly and calcination process. Benefiting from 3D porous configuration with great accessibility, high electrical conductivity, abundant active sites, optimal nitrogen content and strong electronic interactions at the Ni3 Fe/N‐doped graphene heterointerface, the obtained aerogel showed outstanding catalytic performance toward the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). Specifically, it exhibited an overpotential of 239 mV to attain 10 mA cm −2 for OER, simultaneously providing a positive onset potential of 0.93 V within a half‐wave potential of 0.8 V for ORR. Accordingly, when employed in the aqueous ZABs, Ni3 Fe‐GA1 achieved higher power density and superior reversibility than Pt/C−IrO2 catalyst, making it a potential candidate for rechargeable ZABs. Abstract : Ni3 Fe alloy nanoparticles encapsulated in 3D porous N‐doped graphene aerogel with appropriate nitrogen content was synthesized by a facile hydrothermal assembly followed by a calcination process. The strong electronic interactions between Ni3 Fe and N‐doped graphene induces the redistribution of charge on the interface and simultaneously modulates the electronic structure, leading to enhanced electrocatalytic activity for OER and ORR.